PENGARUH KOMITMEN ORGANISASIONAL DAN PERSEPSI DUKUNGAN ORGANISASI TERHADAP TURNOVER INTENTION PADA KARYAWAN PT BANK JATIM CABANG MALANG - Suci, Listia Nurul (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
The purpose of this study to determine the effect of organizational commitment and perceived organizational support on employee turnover intention at PT Bank Jatim Branch Malang. This type of research is explanatory to explain or prove the relationship influence between variables. This research uses quantitative approach by using descriptive statistical analysis of multiple linear regressions. The sampling technique in this research is by simple random sampling. Primary data collection by distributing questionnaires using Likert Scale, secondary data obtained from the company and literature review. The total population of 165 and 62 sample respondents in this research are intended for permanent employees at PT Bank Jatim Branch Malang. The test results showed that organizational commitment variable and perceived organizational support variable negatively and partially significant to the turnover intention variable of employees of PT Bank Jatim Branch of Malang. Keywords:Â Organizational Commitment, Perceived Organizational Support, Turnover Intention, and Bank Employees.